It's the Economy! Perceptions of Host-Countries' Institutions and Individual Life Satisfaction of Intra-European Migrants - Kogan, Irena; Shen, Jing (Frontiers in Sociology, 2019)
By drawing data from the European Social Survey (2008-2016), this study explores how immigrants’ assessments of economy, democracy, and quality of public goods (such as health and education systems) in the receiving societies contribute to their life satisfaction. Results indicate that satisfaction with the economy is the strongest correlate of individual life satisfaction among European immigrants, and this association is particularly pronounced among immigrants from Turkey, Eastern and Southern Europe. Assuming that immigrants compare institutions of their host and home countries when assessing institutional features of the host countries, relative gains in satisfaction with the performance of host-country economy are shown to be associated with particularly higher levels of overall life satisfaction among immigrants from Turkey, Eastern and Southern European countries than the rest of Europe. We conclude that, in relative terms, migrants from countries with less well functioning economies to countries with more favorable economic conditions display higher levels perceived satisfaction with the host country economies, which contributes considerably to their overall life satisfaction.